ETHNO-VETERINARY HERBAL REMEDIES OF GUJJARS AND OTHER FOLKLORE COMMUNITIES OF ALWAR DISTRICT, RAJASTHAN, INDIA - Sanyasi Rao, M. L.; Ramakrishna, N.; Saidulu, Ch. (International Journal of Ayurveda and Pharma Research, 2015)
The present study encompasses the in-depth investigation on Medicinal plants which were used on Ethno-veterinary medicine in the district of Alwar, Rajasthan India. The present ethno-botanical explorations conducted in the Alwar district of Rajasthan revealed that about 37 species of plants belonging to 32 genera under 24 families have been noticed which they use for veterinary health care. A total of 27 healers and herbal practitioners were interviewed during the study. Total of 47 remedies were recorded for 19 veterinary disease conditions of which 21 remedies were recorded under digestive disorders (9 remedies for bloat, 3 stomach pain and 5 for constipation, 3 food poison and 1 diarrhoea) 9 remedies under reproductive problems (3 for anoestrus, 2 for galactagogue, 3 for retained placenta, and 1 for prolapsed uterus). 5 remedies for diseases of sense organs (2 skin infection, 3 for wounds and maggot wounds). 2 remedies were documented under infectious disease (1 for Foot and Mouth Disease, 1 for Foot rot, 2 for Haemorrhagic septicemia). 1 remedy recorded for general fever. Following data includes botanical name of species, family name, vernacular name, plant part used method of medicine and details of the applications. Among the plant parts used in different formulations, leaves are predominantly used and scored number one position followed by fruits, roots/ rhizomes, stem and bark.